Queering religious texts: An exploration of British non-heterosexual Christians’ and Muslims’ strategy of constructing sexuality-affirming hermeneutics. - Yip, A.K.T. (Sage, 2005)
Religious authority figures often use religious texts as the primary basis for censuring homosexuality. In recent years, however, non-heterosexual Christians and Muslims have begun to contest the discursively produced boundary of sexual morality.Drawing upon two research projects on non-heterosexual Christians and Muslims, this article explores the three approaches embedded in this strategy.While acknowledging that homosexuality is indeed portrayed negatively in some parts of religious texts, the participants critique traditional hermeneutics by highlighting its inaccuracy and socio-cultural specificity, and arguing for a contextualized and culturally relevant interpretation. They also critique the credibility of institutional interpretive authority by highlighting its inadequacy and ideology, and relocating authentic interpretive authority to personal experience. Finally, they recast religious texts to construct resources for their spiritual nourishment.This strategy generally reflects the contemporary western religious landscape that prioritizes the authority of the self over that of religious institution.